Combined method of identification of free oscillations of perforated riffled plates - Serhii Kharchenko; Sylwester Samborski; Lukasz Kloda; Farida Kharchenko (Scientific Reports)
Abstract Presented experimental–numerical method of prediction of modal characteristics of rectangular perforated plates with riffles. The technique allows to analyze the oscillation frequency of plates with holes and stamped riffles. The methodology is based on numerical modeling by FE-methods and experiments to obtain the regularities of changes in the natural oscillation frequency of plate. The methodology involves numerical modelling in Abaqus, the adequacy of which is experimentally verified on a vibrometer PSV-500. Experimental studies are conducted on basic plates with elongated holes measuring 3.2 × 20 mm and 5 × 20 mm, as well as riffled plates with similar holes and different riffles. As a result of the research, dependences of the natural oscillation frequency of riffled perforated plates on their parameters are obtained in comparison with unriffled surfaces. The analysis of the obtained models is carried out and the levels of influence of significant parameters of riffled plates on their natural frequency are determined. The dependences of the natural oscillation frequency of plates on the plate thickness, height, pitch and riffles arrangement, as well as the equations describing them are obtained. The greatest influence on the natural frequencies of riffled perforated plates is exerted by: the plate thickness, the pitch arrangement and the riffle’s height. The obtained regularities of the natural oscillation frequencies of riffled perforated plates may allow for predicting the appearance of deformations in the form of cracks between the holes and determining their durability